Pengelolaan Obat di Unit Farmasi RSUD Tengku Sulung - Neneng, Andi; Susmaneli, Herlina; Kiswanto, Kiswanto; Mitra, Mitra; Herniwanti, Herniwanti (Universitas Batanghari Jambi, 2024)
Pharmaceutical service is a direct and responsible service to patients related to pharmaceutical preparations with the intention of achieving definite results to improve the quality of life of patients. The purpose of this study was to obtain in-depth information on drug management in the Pharmacy Unit of RSUD Tengku Sulung. The research method used descriptive qualitative with purposive sampling with the number of informants 7 people. Data collection through in-depth interviews, direct observation and document review using content analysis. The results, on the input component obtained information that the lack of human resources, facilities and infrastructure are inadequate and there is no depot and SIM RS. Policies have been made in the form of Drug Management Guidelines in the Pharmacy Unit. In the process component, information is obtained that selection is based on the hospital formulary and national formulary, planning using the combination method, procurement using e-catalog and direct purchase, receipt is carried out by checking and adjusting the order letter, order invoice, and the drug received, storage based on dosage form, classification of types of drugs, medical devices, B3 and arranged alphabetically with the FIFO and FEFO systems, distribution using individual prescribing and Floor Stock systems, deletion is carried out by involving third parties, control is carried out by controlling drug inventory and quality, administration based on recording, reporting and financial administration. The output component obtained by the availability of drugs is still not effective and efficient. In conclusion, the pharmaceutical supply management system in the Pharmacy unit of RSUD Tengku Sulung is not in accordance with the established standards. Suggestions, the need for additional human resources, the fulfillment of infrastructure such as depot procurement and SIMRS, monitoring and evaluation, improved communication during drug selection and budget planning in the fulfillment of facilities and infrastructure.